The mystery of Frederic Chopin’s Berceuse - Stacy JARVIS (Akofena, 2024)
Abstract: There is an opinion that lullabies are too simplistic in melody, texture, and harmony to warrant detailed and comprehensive analysis. However, in this study, using the analysis of Frederic Chopin’s Berceuse (1844), this viewpoint is refuted. The author concludes that this composition goes beyond the commonly accepted characteristics and standards of the lullaby genre. During the analysis, the research author explores ways to penetrate the ‘messages’ encoded in the pianistic miniature of the composer. Drawing on the philosophy of Theodor Adorno regarding the social aspect of intimacy, it is inferred that despite the traditional inclusion of words in lullabies, Chopin’s ‘song without words’ is unique, lyrical, emotional, melodious, and possesses rich expressive potential for conveying feelings (in emotional nuances) and thoughts (expressed in meaning). The author raises the question of verbalizing musical art as a possibility of elevating music to the realm of language. Chopin's work helps the composer express intimate thoughts about his unsuccessful family and unborn children, nostalgia for a lost family and homeland. The lullaby preserves the son's memory and nostalgia for his Polish family abroad and serves as a means of inculturating the Polish people.